Enhancing the service quality as a strategy of maintaining competitive position in Malaysian telecommunication industry; a focus on Telekom Malaysia Berhad Gajah Berang, Malacca / Norfa Dila Mohd. Noh - Mohd. Noh, Norfa Dila (Faculty of Business and Management, 2001)
Although service quality and customer satisfaction is related concepts, they are not exactly the same things. The customer's perception about service quality is based on long term, cognitive evaluations of TMB's service delivery, where as customer satisfaction is a short term emotional reaction to a specific service experience. Before TMB's customers purchase a service, they have an expectation about service quality that is based on individual needs, past experience, mouth of mouth recommendation and also a TMB's advertising.